Antitumor and Antioxidant Properties of Water-Soluble Polysaccharides from Submerged Mycelium of Flammulina velutipes - L. M. Krasnopolskaya; M. I. Shuktueva; A. V. Avtonomova; M. S. Yarina; B. R. Dzhavakhyan; E. B. Isakova; V. M. Bukchman (Антибиотики и Химиотерапия, 2020)
The aim of the study was to evaluate antitumor and antioxidant properties of water-soluble polysaccharides from submerged mycelium of Flammulina velutipes grown under optimized conditions. The optimization of the nutrient medium composition allowed to increase the biomass yield by more than 2 times (up to 35 g/l) and to reduce the time of the cultivation process. The submerged mycelium of F.velutipes strain Fv-1 contained 14.8% of a water-soluble polysaccharides, 31.6% of proteins, 2.5% of total lipids, vitamins B (B1, B5, Bg). The polysaccharides contained glucose, galactose, fucose, mannose, xylose, rhamnose. The proteins contained all the essential amino acids except for tryptophan. Dry powder of the submerged mycelium, water extract of the mycelium and total fraction of the water-soluble polysaccharides demonstrated the antitumor activity against murine lymphocytic leukemia Р 388 in vivo. The antitumor activity of the substances was mainly due to the polysaccharides, since their purification increased the tumor growth inhibition. The maximum tumor growth inhibition by the water-soluble polysaccharides amounted to 94%. The total fraction of the water-soluble polysaccharides from F.velutipes strain Fv-1 demonstrated antioxidant activity. The antioxidant capacity (AOC) of the water-soluble fraction from F.velutipes was higher than that of the water-soluble polysaccharides from the submerged mycelium of Grifola frondosa, but inferior to the AOC of the water-soluble polysaccharides from the submerged mycelium of Ganoderma lucidum.